การขึ้นรูปไฮดรอกซีอะพาไทต์ชนิดพรุนโดยใช้ไดแคลเซียมฟอสเฟตไดไฮเดรต และไดแคลเซียมฟอสเฟตแอนไฮดรัสจากอุตสาหกรรมกระดูกสัตว์ - พรนภา สุจริตวรกุล (จุฬาลงกรณ์มหาวิทยาลัย, 2000)
Porous hydroxyapatile has been increasingly used as bone filling and bone substitute because of its similarity as bone and a better biocompatibility than that of the other ceramic implants. The implant materials need an appropriate combination between pore size and strength. This requirement can be optimized by the application of fabrication technology. In this work, two methods, slip casting and powder pressing were employed. A mixture of dicalcium phosphate dihydrate (DCPD) and calcium carbonate was used as the casting slurry with hydrogen peroxide as a foaming agent. Sintered cast specimens with inhomogeneous phase distribution were obtained. Phase segregation was due to a big difference in particle size and density of the slurry components. In the pressing method, dicalcium phosphate dihydrate and dicalcium phosphate anhydrous (DCPA) powders were each mixed with calcium carbonate and 0, 5 wt% calcium phosphate glass, pressed into shape and sintered in air at temperatures of 1200 and 1250 ํC, respectively. The chemical characteristics of the porous compacts were determined using x-ray diffraction (XRD) and Fourier-Transform Infrared spectrometer (FT-IR), while the physical characteristics were determined using scanning electron microscopy (SEM), mercury porosimetry and Archimedes method and the mechanical characteristics by an Hounsfield-type testing machine. The typical porous compacts obtained are high-purity HAP and HAP-TCP composite with the following properties: interconnected micro to macroporous structure (1-200 micron in diameter) porosity in the range of 32.59-63.70%, compressive and flexural strengths of 3.93-78.13 and 2.48-17.51 MPa, respectively. In comparison, the specimens prepared from DCPA give much higher mechanical strength than those from DCPD. In this experiment it is found that mechanical strength of the specimens is significantly improved by increasing the forming pressure while the addition of glass promotes the inversion of hydroxyapatite to tricalcium phosphates.